Adipose Tissue Gene Expression of Adiponectin, Tumor Necrosis Factor-α and Leptin in Metabolic Syndrome Patients with Coronary Artery Disease - Gormez, Selcuk; Demirkan, Ayse; Atalar, Fatmahan; Caynak, Baris; Erdim, Refik; Sozer, Volkan; Gunay, Demet; Akpinar, Bellhan; Ozbek, Ugur; Buyukdevrim, Ahmet Sevim (JAPAN SOC INTERNAL MEDICINE, 2011)
Objective Metabolic syndrome (MS) is associated with an increased risk of coronary artery disease (CAD) and type 2 diabetes mellitus (DM). In MS, adipose tissue has been shown to function as a paracrine and an endocrine organ secreting various adipocytokines. In the current study, adiponectin, tumor necrosis factor-alpha (TNF-alpha) and leptin gene expressions in the epicardial adipose tissue (EAT), paracardial adipose tissue (PAT) and subcutaneous adipose tissue (SAT) were investigated in MS patients with CAD and in non-MS patients without CAD. Methods and Results Thirty-seven patients with MS undergoing coronary artery bypass grafting due to CAD (MS group) and twenty-three non-MS patients without CAD undergoing heart valve surgery (control group) were recruited prospectively to the study. Relative gene expressions of adiponectin, TNF-alpha and leptin in EAT, PAT and SAT were compared between two groups of patients. Adiponectin gene expression in EAT and PAT were significantly lower in MS group compared to the control group (p < 0.0001, p=0.04, respectively) while SAT adiponectin gene expression did not differ significantly (p=0.64). TNF-alpha and leptin gene expressions were found to be statistically significantly higher in EAT, PAT and SAT of the MS group (p < 0.0001, for all). Conclusion Our results demonstrate that TNF-alpha and leptin gene expressions increase prominently in the EAT, PAT and SAT while adiponectin gene expression decreases significantly in EAT and PAT in MS patients with CAD. These findings suggest that disturbances in expression of adiponectin, TNF-alpha and leptin in EAT, PAT and SAT might play an important role in MS patients with CAD.
Keywords: metabolic syndrome; atherosclerosis; chemokines; inflammation; genes; IN-VIVO; ADIPOCYTOKINES; PROTEIN; WEIGHT; RISK; General & Internal Medicine